Sensorial characterization of strawberry cultivars - Schuch, Sônia Maria Lobato (2010)
In Rio Grande do Sul, the southernmost state of Brazil, strawberries (Fragaria x ananassa) are cultivated for fresh consumption and agro-industrial processing, with sensory characterization and organoleptic analysis being an important tool for the selection of new strawberry cultivars. We employed sensory analysis, using a panel of 15 evalua- tors trained in sensorial profiling, to evaluate a set of attributes (appearance, aroma, acidity, flavor and texture) of eight strawberry cultivars (Camarosa, Campinas, Chandler, Dover, Oso Grande, Seascape, Verão and Vila Nova). Senso- rial analysis showed differences between the cultivars regarding acidity, appearance, aroma and texture. Seascape, followed by Verão and Oso Grande, showed the best appearance and a very firm texture. Oso Grande, Camarosa and Campinas were the most aromatic. Vila Nova and Verão were the most acidic. Our results indicate that sensorial cha- racterization of these strawberry cultivars using the test attribute profile was efficient as regards the attributes acidity, appearance, aroma and texture.